First records and general distribution of the plane tree lace bug (Corytucha ciliata) and the sycamore seed bug (Belonochilus numenius) in Kosovo - Muja, Ibrahim; Risteski, Mihajlo; Srebrova, Katerina; Sotirovski, Kiril (University of Forestry, Sofia, 2021)
The oriental plane tree (Platanus orientalis L.) is a common natural floristic element in Southern Balkans (Albania, Greece, North Macedonia, Serbia and Kosovo,) and is widely used in urban greenspace, as is also London plane tree (P. x acerifolia), especially in the last 2-3 decades. Unfortunately, both tree species are increasingly threatened by plant pathogenic fungi (Apiognomonia veneta (Sacc. & Speg.) Höhn; Ceratocystis platani (Walter) Engelbrecht & Harrington), as well as insect pests (Corythucha ciliata Say). The invasive plane tree lace bug (C. ciliata) and the sycamore seed bug (Belonochilus numenius Say), are Nearctic insect species which were firstly reported in Europe in 1964 and 2008, respectively. Both have spread in most plane tree regions of Europe and in the Balkans as well. The recent find of the seed bug in North Macedonia (2019) and its widespread presence, as well as omnipresence and high population density of the plane tree lace bug in that country (unpublished), prompted us to inspect urban and peri-urban plane trees in Kosovo, for which there are no previous records of these insects. During early October 2019 we registered presence of both insect species in urban and periurban plane tree populations Kosovo. Specimens were collected from all visited sites in Prishtina, Gjakova, Pegja, Uroshevac and Prizren from leaves and seed balls of P. x acerifolia and in the case of Prishtina from P. orientalis, and were identified in compliance to morphological characteristics typical for C. ciliata and B. numenius. Populations of C. ciliata were generally high, in extreme cases over 200 individuals (adults and larvae of all stages) per individual leaf. Further research is underway for detailed assessment of the distribution of both insect species on the total territory of Kosovo, as well as for establishment of population density, especially of C. ciliata which can pose a serious threat to the health status of plane populations. Although both species are well established and have been overlooked for many years (B. numenius) and many decades (C. ciliata), these are the first records for both the plane tree lace bug and the sycamore seed bug in Kosovo.
Keywords: invasive species, insect pests, Platanus spp.